A Smart Anticorrosive Epoxy Coating Based on Environmental‐Stimuli‐Responsive Copolymer Assemblies for Controlled Release of Corrosion Inhibitors. Issue 7 (7th April 2022) - Cao, Ying; He, Jianmin; Wu, Jianhua; Wang, Xiaoyu; Lu, Wei; Lin, Jingyu; Xu, Yiting; Chen, Guorong; Zeng, Birong; Dai, Lizong
Abstract: Inspired by the various applications of self‐assembled amphiphilic polymers in aqueous solution, a novel "semi‐amphiphilic" copolymer is designed, which can self‐assemble in organic systems by taking advantage of the compatibility difference between epoxy and the units with different structures in the polymer chains. A novel kind of polymer, poly(syringaldehyde methacrylate)‐co‐poly(dopamine methacrylate) is prepared by reversible addition‐fragmentation chain transfer polymerization, which contains aldehyde groups and is further used to prepare the polymer/guanine conjugate by forming the Schiff base. The polymer/guanine conjugate is semi‐amphiphilic, since the compatibility between dopamine methacrylate unit and epoxy is better than that between syringaldehyde methacrylate and epoxy, and therefore assemblies are formed in the organic system when it is added into the epoxy resin to prepare the anti‐corrosive coating. The imine linkage is responsible for the pH‐controlled release of the corrosion inhibiters, namely guanine, from the core of the assemblies. The self‐assembled behaviors of the semi‐amphiphilic copolymer in epoxy are investigated by dynamic light scattering and scanning electron microscopy. The stable encapsule and controlled‐release of the inhibitors are confirmed by UV spectrophotometry. The properties of the smart coatings are comprehensively studied. Abstract : A novel kind of "semi‐amphiphilic" copolymer, which can self‐assemble in organic systems is designed and applied as carriers for corrosion inhibitors. The assemblies formed by the "semi‐amphiphilic" copolymer is pH‐responsive, leading to the controlled and sustainable release of inhibitors once corrosion happened, since corrosion can result in a pH gradient.